The Ups and Downs of Social Comparison and Contrast. (article). - Musseiler , Thomas
Social comparisons influence self-evaluations in multiple ways. Sometimes self-evaluations are assimilated toward a given standard . At other times. They are constructed away from the standard . On the basis of the selected accessibility model (T. Mussweiler , 2003a), the authors hypothesized that assimilation results if judges engage in the comparison of similarity testing and selectively focus on similarities to the standard, whereas contrast occurs if judges engage in dissimilarities testing and selectively focus on differences. If these alternative comparison mechanisms are indeed at play, then assimilative and contrastive social comparisons should be accompanied by diverging information foci on similarities versus differences. Results of 5 studies support this reasoning, demonstrating that assimilation results under conditions that foster similarity testing whereas contrast occurs that under conditions that foster dissimilarity testing. Furthermore, assimilative social comparisons are accompanied by a general informational focus on similarities, whereas contrastive comparisons are accompanied by a focus on differences. -- ( from the author).
Keywords: Psychology-Periodicals.